High-toughness automobile safety belt torsion bar and preparation process thereof

The method of refining grain refinement and applying a vinyl cyclic hyperbranched polysiloxane and graphene oxide-based coating to cold-headed steel rods addresses the toughness and fatigue issues in seat belt torsion bars, improving their mechanical properties and corrosion resistance.

CN119121036APending Publication Date: 2024-12-13JIANGYIN JIXI STANDARD COMPONENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411154781.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional cold-headed steel hot-rolled wire rods used in seat belt torsion bars suffer from insufficient toughness and poor fatigue resistance due to inadequate grain refinement and processing, leading to potential failure during vehicle collisions.

Method used

A method involving remelting with an Al-Ti-B-La-Ce refiner to refine grains, followed by a coating process using a vinyl cyclic hyperbranched polysiloxane and graphene oxide-based coating liquid to enhance mechanical properties and corrosion resistance.

Benefits of technology

The method improves the strength and toughness of the seat belt torsion bars by refining grains and applying a protective coating, enhancing their mechanical properties and resistance to wear and corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005004634230000131
    Figure BDA0005004634230000131
Patent Text Reader

Abstract

The invention relates to the technical field of metallurgy, in particular to a high-toughness automobile safety belt torsion bar and a preparation process thereof. Comprising the following steps: S1) melting pig iron, and sequentially adding an iron-chromium alloy and a silicon-manganese alloy; the basic steel is obtained through smelting, refining slagging-off, gas refining and casting in sequence; (2) under the argon atmosphere, the base steel is remelted, a refiner is added, modification treatment, casting forming, cold heading treatment and annealing are conducted, and base cold heading steel is obtained; s2, (1) the basic cold forging steel is sequentially subjected to hot rolling and air cooling, and a rod material is obtained; (2) the rod material is sequentially subjected to annealing treatment, cooling, acidification, phosphorization and drawing sizing, and a foundation rod is obtained; s3, the surface of the foundation rod is coated with a coating solution, ultraviolet light illumination and drying are carried out, and a coating of 1-2 mm is obtained; therefore, the automobile safety belt torsion bar is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, in particular to a high-toughness automobile safety belt torsion bar and a preparation process thereof. Background Art

[0002] With the rapid development of the automobile industry and the continuous increase in the number of cars, automobile users have increasingly higher requirements for vehicle safety performance. Cold-headed steel hot-rolled wire rods have been widely used in seat belt torsion bars due to their high strength, corrosion resistance, energy saving and environmental protection, low production cost and other advantages. In the prior art, the preparation process of traditional cold-headed steel hot-rolled wire rods is not properly processed in grain refinement, cooling, rolling and other processes, resulting in cold-headed steel hot-rolled wire rods often accompanied by problems such as insufficient toughness, easy fracture, and poor fatigue resistance. This makes the seat belt torsion bar fail to effectively restrain the occupants when the vehicle collides, thereby increasing the risk of occupant injury.

[0003] In summary, it is of great significance to prepare a high-toughness automobile seat belt torsion bar. Summary of the invention

[0004] The purpose of the present invention is to provide a method to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation process of a high-toughness automobile safety belt torsion bar comprises the following steps:

[0007] Step 1: (1) melting pig iron, adding iron-chromium alloy and silicon-manganese alloy in sequence; smelting, refining slag removal, gas refining, and casting to obtain basic steel; (2) remelting the basic steel in an argon atmosphere, adding a refiner, performing a modification treatment, casting, cold heading treatment, and annealing to obtain a basic cold heading steel;

[0008] Step 2: (1) hot rolling and air cooling the basic cold heading steel in sequence to obtain a rod material; (2) annealing, cooling, acidifying, phosphating, and drawing and sizing the rod material in sequence to obtain a basic rod;

[0009] Step 3: Apply coating liquid on the surface of the base rod, irradiate with ultraviolet light, and dry to obtain a coating of 1 to 2 mm; this is used as the automobile seat belt torsion rod.

[0010] More optimally, it is characterized in that the composition of the basic steel includes the following elements, calculated by mass percentage: 0.015% to 0.08% carbon, 0.018% to 0.04% silicon, 0.20% to 0.25% manganese, 0.01% to 0.02% chromium, phosphorus ≤0.015%, sulfur ≤0.015%, and the rest is iron and unavoidable impurities.

[0011] Among them, the base steel is remelted, through which the impurities and gases in the base steel can be removed, the purity of the material can be improved, and thus the mechanical properties and processing properties of the material can be improved. In addition, the remelting treatment can further homogenize the chemical composition and organizational structure of the steel, eliminate the existing segregation and defects, and also provide high-quality steel billets for subsequent refinement and cold heading.

[0012] In a further solution, the cast base steel is subjected to cold heading treatment, and the strength and toughness of the steel are increased through cold deformation, thereby improving the mechanical properties and surface quality. In addition, the cold heading treatment can also improve the surface quality and dimensional accuracy of the product, forming a high-toughness automobile seat belt torsion bar with the required shape and size.

[0013] More optimally, it is characterized in that: in step 1 (1), the smelting temperature is 1550-1650°C, the refining slag temperature is 1500-1550°C, the gas refining is 1550-1600°C; the casting temperature is 1500-1550°C.

[0014] More optimally, it is characterized in that: in step 1 (2), the remelting temperature is 1600-1700° C., and the modification temperature is 1550-1650° C.;

[0015] During the cold heading process, the temperature is 30-40° C., the speed is 70-75 mm / s, and the pressing stress is 800-900 MPa; during the annealing process, the temperature is 550-650° C., and the time is 2-4 hours.

[0016] More optimally, it is characterized in that the mass ratio of the base steel to the refiner is 50:0.05-0.2; and the refiner is Al-Ti-B-La-Ce refiner.

[0017] More optimally, it is characterized in that: the preparation method of the Al-Ti-B-La-Ce refiner comprises the following steps: (1) melting pure aluminum at 660-700°C to obtain aluminum liquid, adding titanium powder, TiB2 powder, potassium fluoroborate, potassium fluorotitanate and the first part of the covering agent to the aluminum liquid in sequence, stirring and reducing at 1000-1100°C to obtain a melt; (2) adding lanthanum powder, cerium powder and the second part of the covering agent to the melt in sequence, stirring evenly at 800-900°C to obtain a melt A; (3) adding the third part of the covering agent to the melt A, alloying at 750-800°C for 1-2 hours; introducing hexachloroethane for refining and slagging, gas refining for 15-30 minutes under an argon atmosphere, casting and forming, and obtaining the Al-Ti-B-La-Ce refiner.

[0018] Among them, adding Al-Ti-B-La-Ce refiner for modification can play a role in refining grains, improving processing performance, and improving the uniformity of materials. Ti, B and other elements in Al-Ti-B-La-Ce refiner are effective grain refiners, which can form a large number of fine particles during the solidification of molten steel, increase the nucleation rate, and refine the grains of steel, thereby significantly improving the strength and toughness of steel. After grain refinement, the cold working performance of steel will also be improved, making the steel more susceptible to plastic deformation during cold working, reducing the tendency of work hardening and cracking. In addition, rare earth elements such as La and Ce in the refiner can also purify molten steel and remove impurities, thereby further improving the purity and uniformity of steel.

[0019] More optimally, it is characterized in that: the Al-Ti-B-La-Ce refiner comprises the following raw materials in parts by weight: 75-80 parts of pure aluminum, 8-10 parts of titanium powder, 5-6 parts of TiB2 powder, 1-1.2 parts of lanthanum powder, 0.5-0.8 parts of cerium powder, 4-5 parts of potassium fluoroborate, 5-6 parts of potassium fluorotitanate, and 3-6 parts of covering agent;

[0020] The covering agent comprises sodium hydroxide, potassium hydroxide and sodium fluoride in a mass ratio of 8 to 9:10 to 11:1.

[0021] More optimally, it is characterized in that: the method for preparing the coating liquid comprises the following steps:

[0022] S1: (1) tri(isoallyloxy)vinylsilane, ethanol, and Speier catalyst are mixed in sequence at 50-60° C. under a nitrogen atmosphere to obtain a solution A; (2) N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, graphene oxide, and ethanol are added to the solution A in sequence at 60-70° C., stirred for 8-9 hours, and filtered to obtain a graphene oxide-siloxane monomer A;

[0023] S2: acetic anhydride, graphene oxide-siloxane monomer A, and tetrakis(trimethylsiloxy)titanium are stirred in a vacuum at 50-70° C. for 1-1.5 hours under an argon atmosphere, and then placed at room temperature for 10-12 hours to obtain a vinyl cyclic hyperbranched polysiloxane;

[0024] S3: (1) Stirring vinyl cyclic hyperbranched polysiloxane, end-containing hydrogen silicone oil, and Speier catalyst for 5 to 10 minutes to obtain modified HBPSi-PDM-SGO; (2) Mixing modified HBPSi-PDM-SGO, dimercaptopropionic acid, azobisisobutyronitrile, and toluene at 50 to 60° C. for 1 to 1.5 hours to obtain a coating liquid.

[0025] In the scheme, the Speier catalyst is chloroplatinic acid.

[0026] More optimally, it is characterized in that: the solution A comprises the following raw materials, by weight: 15 to 20 parts of tri(isoallyloxy)vinylsilane, 30 to 40 parts of ethanol, and 0.1 to 0.8 parts of Speier catalyst; the graphene oxide-siloxane monomer A comprises the following raw materials, by weight: 25 to 30 parts of solution A, 5 to 7 parts of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 30 to 35 parts of ethanol, 5 to 7 parts of graphene oxide; the vinyl cyclic hyperbranched polysiloxane comprises the following raw materials, by weight: 5 to 6 parts of acetic anhydride, 8 to 12 parts of graphene oxide-siloxane monomer A, and 0.7 to 1 part of tetrakis(trimethylsiloxy)titanium; the modified HBPSi-PDM-SGO comprises the following raw materials, by weight: 15 to 20 parts of vinyl cyclic hyperbranched polysiloxane, 3 to 5 parts of terminal hydrogen-containing silicone oil, and 0.1 to 0.8 parts of Speier catalyst;

[0027] The coating liquid comprises the following raw materials, calculated by weight: 12 to 15 parts of modified HBPSi-PDM-SGO, 4 to 5 parts of dimercaptopropionic acid, 1 to 1.5 parts of azobisisobutyronitrile, and 30 to 40 parts of toluene.

[0028] In a further scheme, a coating liquid is prepared and applied to a base rod, which can effectively improve the wear resistance, corrosion resistance, plastic toughness, and surface quality of the base rod. Among them, vinyl cyclic hyperbranched polysiloxane (HBPSi) has a unique three-dimensional network structure, which gives the coating good mechanical strength, wear resistance, and corrosion resistance. At the same time, the silicon oxygen bond (Si-O-Si) in the polysiloxane segment has a high bond energy, which allows the coating to remain stable even at high temperatures. As a nanofiller, graphene oxide (SGO) can significantly improve the hardness and wear resistance of the coating, and its lamellar structure acts as a physical barrier in the coating, effectively blocking the erosion of the substrate by external factors. In addition, the addition of polydimethylsiloxane (PDM) allows the coating to have good flexibility and elasticity while maintaining high strength.

[0029] More optimally, a process for preparing a high-toughness automobile seat belt torsion bar produces an automobile seat belt torsion bar.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. By preparing a refiner to refine the grains, fine grain boundaries are formed. The grain boundaries have an inhibitory effect on dislocation movement, thereby improving the strength of the material; at the same time, fine grains also mean that more stress can be dispersed during deformation, thereby improving toughness.

[0032] 2. By preparing a coating liquid and coating it on a base rod, the vinyl cyclic hyperbranched polysiloxane has a three-dimensional network structure, which can make the base rod have good mechanical strength, wear resistance and corrosion resistance; by introducing graphene oxide, the hardness and wear resistance of the coating can be significantly improved; by introducing polydimethylsiloxane, the coating can have good flexibility and elasticity. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that the following parts are by mass, and the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: In the following embodiments: pure aluminum item number is SBL001-19, purchased from Henan Detong Environmental Protection Technology Co., Ltd.; lanthanum powder with a purity of 99.99% is purchased from Shandong Xiya Chemical Co., Ltd.; cerium powder is 100 mesh, purchased from Huainan Kedi Chemical Technology Co., Ltd.; titanium powder is 60nm, CAS number is 7440-32-6, purchased from Shanghai Mairui Biochemical Technology Co., Ltd.; TiB2 powder has a purity of 99.9%, CAS number is 12045-63-5, purchased from Guangzhou Nano Chemical Technology Co., Ltd. Company; Speier catalyst with a purity of 99%, item number H721046, purchased from Wuhan Xinxin Jiali Biotechnology Co., Ltd.; graphene oxide with a purity of 99%, a lateral size of 0.5-10 μm, purchased from Shanghai Mairui Biochemical Technology Co., Ltd.; terminal hydrogenated silicone oil with a purity of 99%, CAS number 17875-55-7, purchased from Anhui Aiyota Silicone Oil Co., Ltd.; potassium fluoroborate with a purity of 98%, CAS number 14075-53-7, purchased from Hubei Rishengchang New Materials Technology Co., Ltd.; potassium fluorotitanate with a purity of 99%, CAS number 16919-27-0, purchased from Nanjing Chemical Reagent Co., Ltd.

[0035] In the following schemes, the acidification process is: using a hydrochloric acid solution with a concentration of 0.1 mol / L as the acidic solution, soaking the rod material at 35°C for 30 min, and then rinsing with a large amount of deionized water;

[0036] The phosphating process is as follows: 15 parts of disodium hydrogen phosphate, 1.5 parts of sodium nitrate, and 1.2 parts of hydrogen peroxide are mixed in sequence to obtain a phosphating solution; the acidified rod material is immersed at 35° C. for 35 minutes, and then rinsed with a large amount of deionized water.

[0037] The covering agent is composed of sodium hydroxide, potassium hydroxide and sodium fluoride in a mass ratio of 9:10:1.

[0038] In the following implementation method, the composition of the base steel includes the following elements, by mass percentage: 0.05% carbon, 0.03% silicon, 0.225% manganese, 0.015% chromium, 0.01% phosphorus, 0.012% sulfur, and the rest is iron and unavoidable impurities.

[0039] Embodiment 1: A process for preparing a high-toughness automobile safety belt torsion bar, comprising the following steps:

[0040] Step 1: Preparation of Al-Ti-B-La-Ce refiner: (1) 78 parts of pure aluminum are melted at 700°C to obtain aluminum liquid, 9 parts of titanium powder, 5.5 parts of TiB2 powder, 4.5 parts of potassium fluoroborate, 5.5 parts of potassium fluorotitanate, and 1 part of covering agent are added to the aluminum liquid in sequence, and stirred and reduced at 1100°C to obtain a melt; (2) 1.1 parts of lanthanum powder, 0.6 parts of cerium powder, and 1 part of covering agent are added to the melt in sequence, and stirred evenly at 880°C to obtain a melt A; (3) 2 parts of covering agent are added to melt A, and alloying treatment is performed at 800°C for 1.5 hours; hexachloroethane is introduced for refining and slagging, gas refining is performed under argon atmosphere for 20 minutes, and casting is performed to obtain Al-Ti-B-La-Ce refiner;

[0041] Step 2: Preparation of coating liquid: S1: (1) 18 parts of tri(isoallyloxy)vinylsilane, 30 parts of ethanol, and 0.5 parts of Speier catalyst were mixed in sequence at 55° C. under a nitrogen atmosphere to obtain solution A; (2) 6 parts of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 6 parts of graphene oxide, and 30 parts of ethanol were added to 30 parts of solution A in sequence at 65° C., stirred for 8 hours, and filtered to obtain graphene oxide-siloxane monomer A; (3) 5 parts of acetic anhydride, 10 parts of graphene oxide-siloxane monomer A, 0.8 (4) 18 parts of vinyl cyclic hyperbranched polysiloxane, 4 parts of terminal hydrogen silicone oil and 0.5 parts of Speier catalyst were stirred for 10 min to obtain modified HBPSi-PDM-SGO; (5) 13 parts of modified HBPSi-PDM-SGO, 4.5 parts of dimercaptopropionic acid, 1.2 parts of azobisisobutyronitrile and 35 parts of toluene were mixed at 55°C for 1.2 hours to obtain a coating liquid;

[0042] Step 3: Preparation of automobile seat belt torsion bar: S1: (1) Melting pig iron, adding iron-chromium alloy and silicon-manganese alloy in sequence; smelting at 1580°C, refining and slagging at 1550°C, gas refining at 1580°C, and casting at 1500°C to obtain basic steel; (2) In an argon atmosphere, remelting the basic steel at 1650°C, adding a refiner, and performing a deterioration treatment at 1600°C for 2 hours; casting and forming at 1500°C, setting a compressive stress of 850 MPa, performing a cold heading treatment at 35°C at a speed of 75 mm / s, and annealing at 600°C for 4 hours to obtain a basic cold heading steel;

[0043] S2: (1) The basic cold heading steel is sequentially hot rolled at 1050°C for one time, hot rolled at 850°C for two times at a speed of 75 m / s, hot rolled for three times at 850°C, and air-cooled at 700°C at a speed of 1.0°C / s to obtain a rod; (2) The rod is sequentially annealed at 700°C for 12 hours, cooled, acidified, phosphated, and drawn to size to obtain a basic rod; S3: A coating liquid is applied to the surface of the base rod, exposed to ultraviolet light for 2 hours, and dried at 50°C for 12 hours to obtain a 1 mm coating; this is used as a torsion bar for a car seat belt.

[0044] Embodiment 2: A process for preparing a high-toughness automobile safety belt torsion bar, comprising the following steps:

[0045] Step 1: Preparation of Al-Ti-B-La-Ce refiner: (1) Melt 75 parts of pure aluminum at 700°C to obtain aluminum liquid, add 8 parts of titanium powder, 5 parts of TiB2 powder, 4 parts of potassium fluoroborate, 5 parts of potassium fluorotitanate, and 1 part of covering agent to the aluminum liquid in sequence, and stir and reduce at 1100°C to obtain a melt; (2) Add 1 part of lanthanum powder, 0.5 parts of cerium powder, and 1 part of covering agent to the melt in sequence, stir evenly at 880°C to obtain melt A; (3) Add 2 parts of covering agent to melt A, and alloy it at 800°C for 1.5 hours; introduce hexachloroethane for refining and slag removal, gas refine for 20 minutes under argon atmosphere, and cast it to obtain Al-Ti-B-La-Ce refiner;

[0046] Step 2: Preparation of coating liquid: S1: (1) 18 parts of tri(isoallyloxy)vinylsilane, 30 parts of ethanol, and 0.5 parts of Speier catalyst were mixed in sequence at 55° C. under a nitrogen atmosphere to obtain solution A; (2) 6 parts of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 6 parts of graphene oxide, and 30 parts of ethanol were added to 30 parts of solution A in sequence at 65° C., stirred for 8 hours, and filtered to obtain graphene oxide-siloxane monomer A; (3) 5 parts of acetic anhydride, 10 parts of graphene oxide-siloxane monomer A, 0.8 parts of tetrakis(trimethylsiloxy)titanium were stirred in vacuum at 60°C for 1.5 hours under argon atmosphere and allowed to stand at room temperature for 12 hours to obtain vinyl cyclic hyperbranched polysiloxane; (4) 18 parts of vinyl cyclic hyperbranched polysiloxane, 4 parts of terminal hydrogen silicone oil and 0.5 parts of Speier catalyst were stirred for 10 minutes to obtain modified HBPSi-PDM-SGO; (5) 12 parts of modified HBPSi-PDM-SGO, 4 parts of dimercaptopropionic acid, 1 part of azobisisobutyronitrile and 30 parts of toluene were mixed at 50°C for 1 hour to obtain a coating liquid;

[0047] Step 3: Preparation of automobile seat belt torsion bar: S1: (1) Melting pig iron, adding iron-chromium alloy and silicon-manganese alloy in sequence; smelting at 1580°C, refining and slagging at 1550°C, gas refining at 1580°C, and casting at 1500°C to obtain basic steel; (2) In an argon atmosphere, remelting the basic steel at 1600°C, adding a refiner, and performing a deterioration treatment at 1550°C for 2 hours; casting and forming at 1500°C, setting the compressive stress to 850 MPa, performing a cold heading treatment at 35°C at a speed of 75 mm / s, and annealing at 600°C for 4 hours to obtain To the basic cold heading steel; S2: (1) the basic cold heading steel is sequentially hot rolled at 1050°C for one time, hot rolled at 850°C at a speed of 75m / s for two times, hot rolled at 850°C for three times, and air-cooled at 700°C at a speed of 1.0°C / s to obtain a rod; (2) the rod is sequentially annealed at 700°C for 12 hours, cooled, acidified, phosphated, and drawn to size to obtain a basic rod; S3: coating the surface of the base rod with coating liquid, irradiating with ultraviolet light for 2 hours, and drying at 50°C for 12 hours to obtain a 1mm coating; this is used as a car seat belt torsion bar.

[0048] Embodiment 3: A process for preparing a high-toughness automobile safety belt torsion bar, comprising the following steps:

[0049] Step 1: Preparation of Al-Ti-B-La-Ce refiner: (1) 80 parts of pure aluminum are melted at 700°C to obtain aluminum liquid, 10 parts of titanium powder, 6 parts of TiB2 powder, 5 parts of potassium fluoroborate, 6 parts of potassium fluorotitanate, and 1 part of covering agent are added to the aluminum liquid in sequence, and stirred and reduced at 1100°C to obtain a melt; (2) 1.2 parts of lanthanum powder, 0.8 parts of cerium powder, and 1 part of covering agent are added to the melt in sequence, and stirred evenly at 880°C to obtain a melt A; (3) 2 parts of covering agent are added to melt A, and alloying treatment is performed at 800°C for 1.5 hours; hexachloroethane is introduced for refining and slag removal, gas refining is performed in an argon atmosphere for 20 minutes, and casting is performed to obtain an Al-Ti-B-La-Ce refiner;

[0050] Step 2: Preparation of coating liquid: S1: (1) 18 parts of tri(isoallyloxy)vinylsilane, 30 parts of ethanol and 0.5 parts of Speier catalyst were mixed in sequence at 55°C under a nitrogen atmosphere to obtain solution A; (2) 6 parts of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 6 parts of graphene oxide and 30 parts of ethanol were added to 30 parts of solution A in sequence at 65°C, stirred for 8 hours, and filtered to obtain graphene oxide-siloxane monomer A; (3) 5 parts of acetic anhydride, 10 parts of graphene oxide-siloxane monomer A and 0.5 parts of Speier catalyst were mixed in sequence at 55°C to obtain solution A; (4) 10 parts of acetic anhydride, 0.5 parts of acetic anhydride and 0.5 parts of Speier catalyst were mixed in sequence to obtain solution A; (5) 10 parts of acetic anhydride, 0.5 parts of Speier catalyst and 0.5 parts of Speier catalyst were mixed in sequence to obtain solution A; (6) 10 parts of acetic anhydride, 0.5 parts of Speier catalyst and 0.5 parts of Speier catalyst were mixed in sequence to obtain solution A; (7) 10 parts of acetic anhydride, 0.5 parts of Speier catalyst and 0.5 parts of Speier catalyst were mixed in sequence to obtain solution A; (8) 10 parts of acetic anhydride, 0.5 parts of Speier catalyst and 0.5 parts of Speier catalyst were mixed in sequence to obtain solution A; (9) 10 parts of acetic anhydride, 0.5 parts of Speier catalyst and 0.5 parts of Speier catalyst were mixed in sequence to obtain solution A; (10) 10 parts of acetic anhydride, 0.5 parts of Speier catalyst and 0.5 parts of Spe 8 parts of tetrakis(trimethylsiloxy)titanium are stirred in vacuum at 60°C for 1.5 hours under argon atmosphere and placed at room temperature for 12 hours to obtain vinyl cyclic hyperbranched polysiloxane; (4) 18 parts of vinyl cyclic hyperbranched polysiloxane, 4 parts of terminal hydrogen silicone oil and 0.5 parts of Speier catalyst are stirred for 10 minutes to obtain modified HBPSi-PDM-SGO; (5) 15 parts of modified HBPSi-PDM-SGO, 5 parts of dimercaptopropionic acid, 1.5 parts of azobisisobutyronitrile and 40 parts of toluene are mixed at 60°C for 1.5 hours to obtain a coating liquid;

[0051] Step 3: Preparation of automobile seat belt torsion bar: S1: (1) Melting pig iron, adding iron-chromium alloy and silicon-manganese alloy in sequence; smelting at 1580°C, refining and slagging at 1550°C, gas refining at 1580°C, and casting at 1500°C to obtain basic steel; (2) In an argon atmosphere, remelting the basic steel at 1700°C, adding a refiner, and performing a metamorphic treatment at 1650°C for 2 hours; casting and forming at 1500°C, setting a compressive stress of 850 MPa, performing a cold heading treatment at 35°C at a speed of 75 mm / s, and annealing at 600°C for 4 hours to obtain To the basic cold heading steel; S2: (1) the basic cold heading steel is sequentially hot rolled at 1050°C for one time, hot rolled at 850°C at a speed of 75m / s for two times, hot rolled at 850°C for three times, and air-cooled at 700°C at a speed of 1.0°C / s to obtain a rod; (2) the rod is sequentially annealed at 700°C for 12 hours, cooled, acidified, phosphated, and drawn to size to obtain a basic rod; S3: coating the surface of the base rod with coating liquid, irradiating with ultraviolet light for 2 hours, and drying at 50°C for 12 hours to obtain a 1mm coating; this is used as a car seat belt torsion bar.

[0052] Comparative Example 1: Based on Example 1, the remelting process is not introduced, and the other processes remain unchanged, specifically:

[0053] Step 3: Preparation of automobile seat belt torsion bar: S1: (1) Melt pig iron, add iron-chromium alloy and silicon-manganese alloy in sequence; smelt at 1580°C, add refiner in argon atmosphere, perform deterioration treatment at 1600°C for 2 hours, refine and slag at 1550°C, gas refine at 1580°C, cast at 1500°C to obtain basic steel; (2) Set the compressive stress to 850MPa, perform cold heading treatment at 35°C at a speed of 75mm / s, and anneal at 600°C for 4 hours to obtain basic cold heading steel; S2: (1) The basic cold heading steel is sequentially hot rolled at 1050°C for one time, hot rolled at 850°C for two times at a speed of 75 m / s, hot rolled at 850°C for three times, and air-cooled at 700°C at a speed of 1.0°C / s to obtain a rod; (2) the rod is sequentially annealed at 700°C for 12 hours, cooled, acidified, phosphated, and drawn to size to obtain a basic rod; S3: coating the surface of the base rod with a coating liquid, irradiating with ultraviolet light for 2 hours, and drying at 50°C for 12 hours to obtain a coating of 1 mm; this is used as a torsion bar for a car seat belt.

[0054] Comparative Example 2: Based on Example 1, no refiner is added for modification, and the other processes remain unchanged, specifically:

[0055] Step 3: Preparation of automobile seat belt torsion bar: S1: (1) Melt pig iron, add iron-chromium alloy and silicon-manganese alloy in sequence; smelt at 1580°C, refine and slag at 1550°C, gas refine at 1580°C, and cast at 1500°C to obtain basic steel; (2) Set the compressive stress to 850MPa, perform cold heading treatment at 35°C at a speed of 75mm / s, and anneal at 600°C for 4 hours to obtain basic cold heading steel; S2: (1) The basic cold heading steel is sequentially heated at 1050°C and heated to 400°C. The rod is subjected to a first hot rolling at 850°C at a speed of 75 m / s, a second hot rolling at 850°C at a speed of 75 m / s, a third hot rolling at 850°C, and air cooling at 700°C at a speed of 1.0°C / s to obtain a rod; (2) the rod is subjected to an annealing treatment at 700°C for 12 hours, cooling, acidification, phosphating, and drawing and sizing in sequence to obtain a base rod; S3: coating the surface of the base rod with a coating liquid, irradiating with ultraviolet light for 2 hours, and drying at 50°C for 12 hours to obtain a coating of 1 mm; this is used as a torsion bar for a car seat belt.

[0056] Comparative Example 3: Based on Example 1, the coating liquid ratio was changed, and the other processes remained unchanged. Specifically:

[0057] Step 2: Preparation of coating liquid: S1: (1) 18 parts of tri(isoallyloxy)vinylsilane, 30 parts of ethanol and 0.5 parts of Speier catalyst were mixed in sequence at 55°C under a nitrogen atmosphere to obtain solution A; (2) 6 parts of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 6 parts of graphene oxide and 30 parts of ethanol were added to 30 parts of solution A at 65°C in sequence, stirred for 8 hours, and filtered to obtain graphene oxide-siloxane monomer A; (3) 5 parts of acetic anhydride, 10 parts of graphene oxide-siloxane monomer A and 0.8 parts of tetrakis(trimethylsiloxy)titanium were stirred in a vacuum at 60°C under an argon atmosphere for 1.5 hours, and allowed to stand at room temperature for 12 hours to obtain vinyl cyclic hyperbranched polysiloxane; (4) 18 parts of vinyl cyclic hyperbranched polysiloxane, 4 parts of terminal hydrogenated silicone oil and 0.5 parts of Speier catalyst were stirred for 10 minutes to obtain a coating liquid.

[0058] Comparative Example 4: Based on Example 1, the coating liquid is not applied on the base rod, and the other processes remain unchanged. Specifically:

[0059] Step 3: Preparation of automobile seat belt torsion bar: S1: (1) Melt pig iron, add iron-chromium alloy and silicon-manganese alloy in sequence; smelt at 1580°C, refine and slag at 1550°C, gas refine at 1580°C, and cast at 1500°C to obtain basic steel; (2) Weigh basic steel and refiner in a mass ratio of 50:0.12, remelt the basic steel at 1450°C, add refiner, perform modification at 1500°C, refine and slag at 1500°C, gas refine at 1600°C, and cast at 1500°C. , setting the compressive stress to 850 MPa, cold heading treatment was carried out at 35°C at a speed of 75 mm / s, and annealing was carried out at 600°C for 4 hours to obtain basic cold heading steel; S2: (1) The basic cold heading steel was sequentially hot rolled at 1050°C for a first time, hot rolled at 850°C at a speed of 75 m / s for a second time, hot rolled at 850°C for a third time, and air-cooled at 700°C at a speed of 1.0°C / s to obtain a rod; (2) The rod was sequentially annealed at 700°C for 12 hours, cooled, acidified, phosphated, and drawn to obtain a car seat belt torsion bar.

[0060] Testing experiment: The preparation process of a high-toughness automobile seat belt torsion bar prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was used to test its performance: (1) The basic rods prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were referred to the national standard "GB / T50081-2019" to test the toughness performance of the samples; (2) The automobile seat belt torsion bars prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were referred to the national standard "GB / T 10125-2021" and 50 g / L of sodium chloride was selected to test their corrosion resistance at 35°C, and the solution pH was 7.

[0061]

[0062] Table 1

[0063] Result analysis: According to the data analysis in Table 1 above, it can be seen that the present invention performs a modification treatment by remelting and adding a refiner, and effectively reduces impurities and defects in the raw materials through grain refinement, improves the uniformity and density of the material, and thus improves the corrosion resistance of the material to a certain extent. In addition, the fine grains can also disperse more stress during the deformation process, thereby improving the toughness; the corrosion resistance of the material can be improved by applying the HBPSi-PDM-SGO coating liquid; by adding dimercaptopropionic acid and azobisisobutyronitrile when preparing the coating liquid and initiating it under ultraviolet light, the problem of decreased dispersibility of graphene oxide caused by excessive amount can be compensated.

[0064] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for preparing a high-toughness automobile safety belt torsion bar, characterized in that: The following steps are involved: Step 1: (1) melting pig iron, and adding iron-chromium alloy and silicon-manganese alloy in sequence; The base steel is obtained by smelting, refining, slagging, gas refining, and casting in sequence; (2) in an argon atmosphere, the base steel is remelted, a refiner is added, the base steel is modified, cast, cold-headed, and annealed to obtain a base cold-headed steel; Step 2: (1) hot rolling and air cooling the basic cold heading steel in sequence to obtain a rod material; (2) annealing, cooling, acidifying, phosphating, and drawing and sizing the rod material in sequence to obtain a basic rod; Step 3: Apply coating liquid on the surface of the base rod, irradiate with ultraviolet light, and dry to obtain a coating of 1 to 2 mm; this is used as the automobile seat belt torsion rod.

2. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 1, characterized in that: The composition of the basic steel includes the following elements, calculated by mass percentage: 0.015% to 0.08% carbon, 0.018% to 0.04% silicon, 0.20% to 0.25% manganese, 0.01% to 0.02% chromium, phosphorus ≤ 0.015%, sulfur ≤ 0.015%, and the rest is iron and unavoidable impurities.

3. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 1, characterized in that: In step 1 (1), the smelting temperature is 1550-1650°C, the refining slag temperature is 1500-1550°C, the gas refining temperature is 1550-1600°C; and the casting temperature is 1500-1550°C.

4. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 1, characterized in that: In step 1 (2), the remelting temperature is 1600-1700° C., and the modification temperature is 1550-1650° C.; During the cold heading process, the temperature is 30-40° C., the speed is 70-75 mm / s, and the pressing stress is 800-900 MPa; during the annealing process, the temperature is 550-650° C., and the time is 2-4 hours.

5. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 1, characterized in that: The mass ratio of the base steel to the refiner is 50:0.05-0.2; the refiner is Al-Ti-B-La-Ce refiner.

6. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 5, characterized in that: The preparation method of the Al-Ti-B-La-Ce refiner comprises the following steps: (1) melting pure aluminum at 660-700° C. to obtain aluminum liquid, sequentially adding titanium powder, TiB2 powder, potassium fluoroborate, potassium fluorotitanate and a first part of a covering agent into the aluminum liquid, stirring and reducing at 1000-1100° C. to obtain a melt; (2) sequentially adding lanthanum powder, cerium powder and a second part of a covering agent into the melt, stirring evenly at 800-900° C. to obtain a melt A; (3) adding a third part of a covering agent into the melt A, performing an alloying treatment at 750-800° C. for 1-2 hours; introducing hexachloroethane for refining and slagging, gas refining for 15-30 minutes in an argon atmosphere, and casting to obtain the Al-Ti-B-La-Ce refiner.

7. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 6, characterized in that: The Al-Ti-B-La-Ce refiner comprises the following raw materials in parts by weight: 75-80 parts of pure aluminum, 8-10 parts of titanium powder, 5-6 parts of TiB2 powder, 1-1.2 parts of lanthanum powder, 0.5-0.8 parts of cerium powder, 4-5 parts of potassium fluoroborate, 5-6 parts of potassium fluorotitanate, and 3-6 parts of covering agent; The covering agent comprises sodium hydroxide, potassium hydroxide and sodium fluoride in a mass ratio of 8 to 9:10 to 11:

1.

8. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 1, characterized in that: The method for preparing the coating liquid comprises the following steps: S1: (1) tri(isoallyloxy)vinylsilane, ethanol, and Speier catalyst are mixed in sequence at 50-60° C. under a nitrogen atmosphere to obtain a solution A; (2) N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, graphene oxide, and ethanol are added to the solution A in sequence at 60-70° C., stirred for 8-9 hours, and filtered to obtain a graphene oxide-siloxane monomer A; S2: acetic anhydride, graphene oxide-siloxane monomer A, and tetrakis(trimethylsiloxy)titanium are stirred in a vacuum at 50-70° C. for 1-1.5 hours under an argon atmosphere, and then placed at room temperature for 10-12 hours to obtain a vinyl cyclic hyperbranched polysiloxane; S3: (1) Stirring vinyl cyclic hyperbranched polysiloxane, end-containing hydrogen silicone oil, and Speier catalyst for 5 to 10 minutes to obtain modified HBPSi-PDM-SGO; (2) Mixing modified HBPSi-PDM-SGO, dimercaptopropionic acid, azobisisobutyronitrile, and toluene at 50 to 60° C. for 1 to 1.5 hours to obtain a coating liquid.

9. The process for preparing a high-toughness automobile safety belt torsion bar according to claim 8, characterized in that: The solution A comprises the following raw materials, by weight: 15 to 20 parts of tri(isoallyloxy)vinylsilane, 30 to 40 parts of ethanol, and 0.1 to 0.8 parts of Speier catalyst; the graphene oxide-siloxane monomer A comprises the following raw materials, by weight: 25 to 30 parts of solution A, 5 to 7 parts of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 30 to 35 parts of ethanol, and 5 to 7 parts of graphene oxide; the vinyl cyclic hyperbranched polysiloxane comprises the following raw materials, by weight: 5 to 6 parts of acetic anhydride, 8 to 12 parts of graphene oxide-siloxane monomer A, and 0.7 to 1 part of tetrakis(trimethylsiloxy)titanium; The modified HBPSi-PDM-SGO comprises the following raw materials, by weight: 15 to 20 parts of vinyl cyclic hyperbranched polysiloxane, 3 to 5 parts of terminal hydrogen-containing silicone oil, and 0.1 to 0.8 parts of Speier catalyst; The coating liquid comprises the following raw materials, calculated by weight: 12 to 15 parts of modified HBPSi-PDM-SGO, 4 to 5 parts of dimercaptopropionic acid, 1 to 1.5 parts of azobisisobutyronitrile, and 30 to 40 parts of toluene.

10. An automobile safety belt torsion bar prepared according to the process for preparing a high-toughness automobile safety belt torsion bar according to any one of claims 1 to 9.